THE EFFECT OF SELF ESTEEM AND LOCUS OF CONTROL ON DYSFUNCTIONAL AUDIT BEHAVIOR - Apry Linda Diana; Mochamad Yusuf; Aina M (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This research aims to determine the effect of Self Esteem (X1) and Locus Of Control (X2) on dysfunctional audit behavior (Y). Quantitative research using primary data. This study uses a questionnaire with a Likert scale to measure variables to collect data. The saturated sampling methodology was used in the sampling procedure, namely auditors who worked at KAP Bharata, Arifin, Mumajad, and Sayuti (BAMS) with a total sample of 51 respondents in this study. The data analysis method uses moderation regression analysis with the Jamovi 2.4.8 analysis tool. The results of this research state that (1) Self Esteem has no effect on dysfunctional audit behavior (2) external Locus Of Control has a negative and significant effect on dysfunctional audit behavior.